PENGARUH PEMBERIAN TRANS FATTY ACID (TFA) DARI MARGARIN DAN MINYAK KELAPA SAWIT YANG DIPANASKAN BERULANG TERHADAP KADAR GLUKOSA DARAH PUASA PADA TIKUS WISTAR - Retno Larasati; Bambang Wirjatmadi; Merryna Adriani (The Indonesian Journal of Public Health, 2016)
The purpose of this study was to know differences in fasting blood glucose levels among both the control and treatment groups were given Trans Fatty Acid of groceries margarine and oil is heated rapidly. This research is true experimental design to study Post Test Only Control Group Design. The sample size in this study was 25 rats wistar strain males were divided into 5 groups: the first group was the control, the second group by of margarine that is heated by the content of TFA 1%, the third group by the addition palm oil, which is heated repeats to content TFA 1%, the fourth group by margarine are heated with TFA content of 2%, and the fifth group by the addition of palm oil, which is heated repeats to the TFA content of 2%. Treatment was given for 4 weeks, after the laboratory examination of fasting blood glucose at the end of the treatment. Data fasting blood glucose levels in all groups were tested by one-way ANOVA with 95% confidence level. The results showed that TFA may increase the levels of fasting blood glucose treatment groups compared with the control group, and the differences in levels of fasting blood glucose between treatment groups was not influenced by the amount of content TFA but due to different types of TFA given that of margarine and palm oil that is heated Repeat.Keywords: fasting glucose, TFA, margarine, oil heated, rats